Penilaian Tingkat Kerentanan Air Tanah Terhadap Pencemaran dengan Metode Simple Vertical Vulnerability (SVV) Di Kecamatan Bandar Kedung Mulyo Kabupaten Jombang - Ma'arif, Mohammad Syaifuddin; Siswoyo, Hari; Hendrawan, Andre Primantyo (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
Bandar Kedung Mulyo District is an area at risk of groundwater pollution due to agricultural activities involving pesticide use and improper disposal of domestic waste. Preventive measures are necessary to protect groundwater from contaminants. One approach is to assess groundwater vulnerability using the SVV Method. This research aims to evaluate the SVV index as an assessment of groundwater vulnerability derived from parameters such as the thickness of the unsaturated zone, percolation value, and the type of material in the saturated zone. The research results indicate variations in groundwater vulnerability levels, with SVV index values ranging from 11.55 to 47.89 over the five-month study period. There are three classifications of groundwater vulnerability levels: medium (35-65) and high (24-35) with an area percentage of 9 – 10% each. Very high vulnerability (≤ 24) dominates with a percentage of 81 – 82% of the area. The percentage of areas with very high vulnerability decreased, while areas with medium and high vulnerability increased each month. This is due to the decreasing depth of groundwater each month.